Adapting the endoplasmic reticulum proteostasis rescues epilepsy-associated NMDA receptor variants - Zhang Pei-pei; Benske Taylor M.; Ahn Lucie Y.; Schaffer Ashleigh E.; Paton James C.; Paton Adrienne W.; Mu Ting-wei; Wang Ya-juan (Acta Pharmacologica Sinica, 2024)
The GRIN genes encoding N-methyl-D-aspartate receptor (NMDAR) subunits are remarkably intolerant to variation. Many pathogenic NMDAR variants result in their protein misfolding, inefficient assembly, reduced surface expression, and impaired function on neuronal membrane, causing neurological disorders including epilepsy and intellectual disability. Here, we investigated the proteostasis maintenance of NMDARs containing epilepsy-associated variations in the GluN2A subunit, including M705V and A727T. In the transfected HEK293T cells, we showed that the two variants were targeted to the proteasome for degradation and had reduced functional surface expression. We demonstrated that the application of BIX, a known small molecule activator of an HSP70 family chaperone BiP (binding immunoglobulin protein) in the endoplasmic reticulum (ER), dose-dependently enhanced the functional surface expression of the M705V and A727T variants in HEK293T cells. Moreover, BIX (10 μM) increased the surface protein levels of the M705V variant in human iPSC-derived neurons. We revealed that BIX promoted folding, inhibited degradation, and enhanced anterograde trafficking of the M705V variant by modest activation of the IRE1 pathway of the unfolded protein response. Our results suggest that adapting the ER proteostasis network restores the folding, trafficking, and function of pathogenic NMDAR variants, representing a potential treatment for neurological disorders resulting from NMDAR dysfunction.